250 kWth high pressure pilot demonstration of the syngas chemical looping system for high purity H2 production with CO2 capture. (15th November 2018) - Hsieh, Tien-Lin; Xu, Dikai; Zhang, Yitao; Nadgouda, Sourabh; Wang, Dawei; Chung, Cheng; Pottimurthy, Yaswanth; Guo, Mengqing; Chen, Yu-Yen; Xu, Mingyuan; He, Pengfei; Fan, Liang-Shih; et al.
Highlights: World's first chemical looping pilot plant utilizing moving bed reactors. Achieved near-full conversion of coal-derived syngas in the moving bed reducer. Achieved 99% purity hydrogen production with in-situ carbon capture. Validated operational results by ASPEN process simulation. Abstract: Chemical looping combustion (CLC) is an advanced technology for converting fossil fuel while achieving in-situ CO2 capture. The high purity CO generated in the combustion product stream is sequestration/utilization ready, which makes chemical looping one of the most attractive carbon emission control technology. In this paper, the authors present the design, simulation and experimental operation results of the 250 kWth high pressure syngas chemical looping (SCL) pilot plant. The pilot plant's unique countercurrent moving bed design allows near-full conversion of coal-derived syngas with simultaneous production of high purity, carbon-free H2 . Critical aspects of the design efforts, including heat and material balances, reactor sizing approach and solid flow control and measurement devices are presented. An ASPEN Plus® model is constructed to predict the gas and solid conversions of the SCL process the gas and solid conversions of the SCL process under different experimental conditions. The highest syngas conversion achieved was 97.95% with 16.03% oxygen carrier conversion, which were close to the thermodynamic limits for both the gas and solid phases in the reducer. Differences between the experimental results and predicted conversion values were more significant under conditions with lower oxygen carrier to fuel ratio. Greater than 99% purity H2 was produced from the moving bed oxidizer, and the scalability and feasibility of SCL process were successfully demonstrated.